De "Kritieker". - Hof ter Nederloo, Sint-Pieters-Leeuw; BBL (Bank Brussel Lambert) Brussel (Sint-Pieters-Leeuw : De Vrienden van Nederloo, 1990)
De "Kritieker", Hof ter Nederloo, Sint-Pieters-Leeuw, 16 mei 1990 - 24 juni 1990
Bervoets, Fred ; Boffin, Fred ; Bolle, Jos ; Bouttens, Philippe ; Derore, Joël ; Devreux, Pierre ; Dondeyne, Luc ; Gysels, Marc ; Lemmens, Dirk ; Maieu, Frank ; Mertens, Hendirk ; Minnaert, Frans ; Snauwaert, Jef ; Stenmans, Eric ; Szymkowicz, Charles ; Van Breedam, Camiel ; Van Ruysevelt, Luc ; Vanwijnendael, Sylvain ; Vermeersch, Rik ; Vertongen, Frits
biografie
boek